(untitled) (Alternautas, 2022)
COVID-19 arrived in Latin America in late-February 2020, with the first registered case in São Paulo, Brazil. By late-July, the region had the most cases of any region in the world. By April 2021, Latin America had been hit by its third wave of the pandemic, registering more than 57 million cases and 1.3 million deaths. This introduction to Alternautas’ Special Issue on Critical Perspectives on COVID-19 in Latin America provides the backdrop of the coronavirus pandemic for the rest of the issue. It traces the global reverberations of COVID-19 and explores how they played out in Latin America, before then summarising the contributions of each of the articles in the issue in turn.